Simulation of the impact of the atmospheric weather state on the efficiency of functioning of solar thermal and power plants - N. I. Moskalenko; A. R. Akhmetshin; Ya. S. Safiullina; I. R. Dodov; M. S. Khamidullina (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Determine the impact of the meteorological state of the atmosphere on the efficiency of the functioning of solar thermal and power plants. Modeling the molecular absorption of solar radiation by the atmosphere. Modeling the optical characteristics of the gaseous components of the atmosphere, atmospheric aerosol and clouds.METHODS. A method for numerical modeling of incoming solar radiation fluxes their functioning to determine the efficiency of solar thermal and power plants. The solar fluxes are calculated by stacking layers in a multi-stream approximation, taking into account the multi-tiered cloud cover and the probability of overlapping the sky with clouds. The absorption of radiation by the gaseous phase of the atmosphere is taken into account by the method of equivalent mass in an inhomogeneous atmosphere. The optical characteristics of the dispersed phase of the atmosphere are calculated using the Mie theory.RESULTS. An electronic database has been created on the optical characteristics of the gaseous components of the atmosphere, the optical characteristics of atmospheric aerosol and clouds. The effect of anthropogenic impact on the flux of solar radiation falling on the underlying surface is taken into account. The developed modeling takes into account the effect of humidity on the optical characteristics of atmospheric aerosol and its multicomponent composition, depending on the location of the power plant.CONCLUSION. The information necessary for numerical modeling of meteorological effects on the functioning of solar thermal and power plants is generalized. When calculating solar radiation fluxes, direct illumination of the light-receiving surface by solar radiation, scattered radiation by atmospheric aerosol and clouds are taken into account.